2010
DOI: 10.1590/s1516-89132010000100011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation on the Pathogenesis of Streptococcus agalactiae in Nile Tilapia (Oreochromis niloticus)

Abstract: The pathogenesis of a Streptococcus agalactiae was evaluated in a three-period experiment. Two groups of 40 fishes were intraperitoneally (i.p.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(23 citation statements)
references
References 20 publications
2
19
0
2
Order By: Relevance
“…The present study explored the susceptibility and pathogenesis of Queensland grouper to infection by GBS via different routes of exposure and in order to fulfil Koch's postulates and confirm the previous hypothesis that S. agalactiae was causative for the wild fish mortality. Previous studies have demonstrated the susceptibility of Nile and red tilapia to virulent GBS isolates in experimental injection trials (Evans et al , 2004Chen et al 2007;Inocente Filho et al 2009;Pretto-Giordano et al 2010;Abuseliana et al 2011). Interestingly, of the two surviving fish from the injection challenge trial (10 3 cfu fish À1 ), only one fish had gross clinical signs of bacterial infection (bilateral exophthalmos and a congested anus), but both were PCRpositive, and histopathology showed Gram-Glynnpositive bacteria in stained tissues.…”
Section: Immunohistochemistry On Queensland Grouper Tissuesmentioning
confidence: 95%
“…The present study explored the susceptibility and pathogenesis of Queensland grouper to infection by GBS via different routes of exposure and in order to fulfil Koch's postulates and confirm the previous hypothesis that S. agalactiae was causative for the wild fish mortality. Previous studies have demonstrated the susceptibility of Nile and red tilapia to virulent GBS isolates in experimental injection trials (Evans et al , 2004Chen et al 2007;Inocente Filho et al 2009;Pretto-Giordano et al 2010;Abuseliana et al 2011). Interestingly, of the two surviving fish from the injection challenge trial (10 3 cfu fish À1 ), only one fish had gross clinical signs of bacterial infection (bilateral exophthalmos and a congested anus), but both were PCRpositive, and histopathology showed Gram-Glynnpositive bacteria in stained tissues.…”
Section: Immunohistochemistry On Queensland Grouper Tissuesmentioning
confidence: 95%
“…Os sinais clínicos incluem anorexia, escurecimento da pele, natação errática, letargia, curvatura do corpo, exoftalmia e opacidade de córnea uni ou bilateral, sufusões no opérculo e base das nadadeiras, ulceração da epiderme e morte (TRABULSI; ALTERTHUM, 2008). As lesões internas são caracterizadas por congestão brânquial, hepatomegalia acompanhada de congestão, ascite, esplenomegalia e encefalomalácia (SALVADOR et al, 2003;FIGUEIREDO et al, 2006;PRETTO-GIORDANO et al, 2010).…”
Section: Introductionunclassified
“…External analysis showed clinical signs of disease, foremost among them skin hemorrhages, corneal opacity, body ulceration, liver discolouration, frayed fins and intestine and vesicle inflammation, these abnormalities are considered as the main symptoms of infection reported by Giordano, et al [17,26,27], who observed signs such as skin alterations, anorexia, exophthalmia, corneal opacity, extension of the visceral cavity, bleeding and abdominal inflammation, hepatomegaly and splenomegaly. According to Soto [28] it is proven that bacteria are the cause of epithelial hyperplasia in gills, splenomegaly, renomegaly and necrosis in internal organs, mainly in spleen, heart, liver, kidney, brain and musculature.…”
Section: Discussionmentioning
confidence: 89%
“…It has a prevalence of 40% and 70% in stages of fry, juvenile and fattening. It is also reported in several species of fish around the world, due to its geographic distribution includes regions with temperate and tropical climate, as presented by Brazil, China, Malaysia and the United States [16][17][18]. Some diseases are caused by not applying sanitary protocols on growing farms, as well as the use of antibiotics as an almost mandatory preventive or corrective practice.…”
Section: Introductionmentioning
confidence: 99%